"BUAYA DANAU KARI" CERITA RAKYAT MELAYU KUANTAN RIAU SUATU TINJAUAN ESTETIS - AS, Efrizal (Jurnal Ilmu Budaya, 2009)
This writing deals with a folklore, found in kuansing Riau, entitles "Buaya Danau Kari". This folklor is viewed from its aesthetic value. Aesthetically this story brings various feelings to its readers/lieteners for they may feel anxious, sad, shock, happy or painful. Those feeling occur through the characters and events which at the same time, entertain them with its beauty.